Large-Format Additive Manufacturing and Machining Using High-Melt-Temperature Polymers. Part I: Real-Time Particulate and Gas-Phase Emissions - Stefaniak, Aleksandr B; Bowers, Lauren N; Martin, Jr, Stephen B; Hammond, Duane R; Ham, Jason E; Wells, J R; Fortner, Alyson R; Knepp, Alycia K; du Preez, Sonette; Pretty, Jack R; Roberts, Jennifer L; du Plessis, Johan L; et al. (ACS Chemical Health & Safety., 2021)
The literature on emissions during material extrusion additive manufacturing with 3-D printers is expanding; however, there is a paucity of data for large-format additive manufacturing (LFAM) machines that can extrude high-melt-temperature polymers. Emissions from two LFAM machines were monitored during extrusion of six polymers: acrylonitrile butadiene styrene (ABS), polycarbonate (PC), high-melt-temperature polysulfone (PSU), poly(ether sulfone) (PESU), polyphenylene sulfide (PPS), and Ultem (poly(ether imide)). Particle number, total volatile organic compound (TVOC), carbon monoxide (CO), and carbon dioxide (CO ) concentrations were monitored in real-time. Particle emission rate values (no./min) were as follows: ABS (1.7 × 10 to 7.7 × 10 ), PC (5.2 × 10 to 3.6 × 10 ), Ultem (5.7 × 10 to 3.1 × 10 ), PPS (4.6 × 10 to 6.2 × 10 ), PSU (1.5 × 10 to 3.4 × 10 ), and PESU (2.0 to 5.0 × 10 ). For print jobs where the mass of extruded polymer was known, particle yield values (g extruded) were as follows: ABS (4.5 × 10 to 2.9 × 10 ), PC (1.0 × 10 to 1.7 × 10 ), PSU (5.1 × 10 to 1.2 × 10 ), and PESU (0.8 × 10 to 1.7 × 10 ). TVOC emission yields ranged from 0.005 mg/g extruded (PESU) to 0.7 mg/g extruded (ABS). The use of wall-mounted exhaust ventilation fans was insufficient to completely remove airborne particulate and TVOC from the print room. Real-time CO monitoring was not a useful marker of particulate and TVOC emission profiles for Ultem, PPS, or PSU. Average CO and particle concentrations were moderately correlated ( = 0.76) for PC polymer. Extrusion of ABS, PC, and four high-melt-temperature polymers by LFAM machines released particulate and TVOC at levels that could warrant consideration of engineering controls. LFAM particle emission yields for some polymers were similar to those of common desktop-scale 3-D printers.